A novel zinc-binding fold in the helicase interaction domain of the Bacillus subtilis DnaI helicase loader. - Loscha, K; Jaudzems, K; Ioannou, C; Su, X; Hill, F; Otting, G; Dixon, N; Liepinsh, E (2009)
The helicase loader protein DnaI (the Bacillus subtilis homologue of Escherichia coli DnaC) is required to load the hexameric helicase DnaC (the B. subtilis homologue of E. coli DnaB) onto DNA at the start of replication. While the C-terminal domain of DnaI belongs to the structurally well-characterized AAA+ family of ATPases, the structure of the N-terminal domain, DnaI-N, has no homology to a known structure. Three-dimensional structure determination by nuclear magnetic resonance (NMR) spectroscopy shows that DnaI presents a novel fold containing a structurally important zinc ion. Surface plasmon resonance experiments indicate that DnaI-N is largely responsible for binding of DnaI to the hexameric helicase from B. stearothermophilus, which is a close homologue of the corresponding much less stable B. subtilis helicase.